2020
DOI: 10.5897/err2020.3949
|View full text |Cite
|
Sign up to set email alerts
|

The use of contingency contracting in educational settings: A review of the literature

Abstract: Respecting individual differences among students and meeting their unique needs may be one of the greatest challenges faced by teachers. When having a heterogeneous group of students, teachers need to consider a variety of instructional methods. The literature details a large number of teaching strategies supported by research findings, and the purpose of this review is to add to the literature by highlighting important information obtained from research on contingency contracting. This information includes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The study also showed that Contingency Management Technique (CMT) has effect on the study habits among students. The empirical studies confirmed that CMT is effective in increasing inactive behaviour of academic and non academic activities among students (Alwahbi, 2020;Irons et al, 2013). It was also effective in reducing truant behaviour which may affect their study habit in the school (Josephine, 2014;Oliha, 2013;Josephine & Audu, 2013)…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study also showed that Contingency Management Technique (CMT) has effect on the study habits among students. The empirical studies confirmed that CMT is effective in increasing inactive behaviour of academic and non academic activities among students (Alwahbi, 2020;Irons et al, 2013). It was also effective in reducing truant behaviour which may affect their study habit in the school (Josephine, 2014;Oliha, 2013;Josephine & Audu, 2013)…”
Section: Discussionmentioning
confidence: 89%
“…Research evidences have shown that CMT reduce negative behaviour to good behaviour (Pringsheim et al (2019). Similarly, this same technique is also enhancing the positive behaviour (Alwahbi, 2020). To the best knowledge of the researcher, no study has combines the two counselling techniques on students study habit in Lagos State.…”
Section: Introductionmentioning
confidence: 99%
“…Information about tenders, along with supporting documents, is shared with the general public (Schomaker, 2020). This may include the project rationale, basic cost and budget information, technical documents and feasibility studies, notification of procurement plans, procurement methods, contracts awarded, contractor names, contract renewals, performance indicators, as well as appeals and procurement decisions (Alwahbi, 2020).…”
Section: Open Contractingmentioning
confidence: 99%
“…Di sini konselor dan siswa juga menentukan waktu berjalannya kontrak dan berakhirnya kontrak. Lalu, kontrak tersebut bersama-sama disepakati konselor dan siswa dengan menyertakan identitas diri dan tanda tangan yang bersangkutan (Alwahbi, 2020;Rahmadhony, 2019).…”
Section: Pembinaanunclassified